ANALISIS KEBUTUHAN LUASAN RUANG TERBUKA HIJAU KOTA MANADO BERDASARKAN FUNGSI PENYEDIA OKSIGEN - Fadli Rahman; Josephus I. Kalangi; Fabiola B. Saroinsong (COCOS, 2017)
AbstractIncreased population indirectly resulted in the development of urban areas physically and tends to alter green open spaces into built areas to meet the needs and improve services to the population. As a result there is an increase in air temperature, decrease in ground water quality and urban air quality, and high noise level. The existence of urban green open space arrangement can overcome the development as well as to overcome the ecological impact of various disruption of human activities on the natural process in the City of Manado. Then to realize the ecological balance in the Manado city, there is need of green open space development approach that refers to the area and the need of oxygen. This study aims to calculate the area of green open space needed by Manado City based on oxygen supply function. Data analysis of green open space requirement based on area according to Law Number 26 Year 2007 and based on oxygen requirement using Gerakis formula (1974) modified by Wisesa (1998). The results show the green open spaces needed in Manado City area of 2953.45 ha. In meeting the needs of green open spaces Manado City based on the oxygen provider function then everyone is required to plant 3 trees, on an area of 25 m2.Keywords: green open space, oxygen demand, Manado City.